2011
DOI: 10.1097/inf.0b013e3181fefdee
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Rotavirus-associated Acute Gastroenteritis Following Introduction of Rotavirus Vaccine Into Australia's National Childhood Vaccine Schedule

Abstract: : Early evidence from the NIP in Australia has demonstrated high rotavirus coverage with both RV1 and RV5. The introduction of both vaccines has been associated with a marked reduction in gastroenteritis admissions, supportive of both direct vaccine protection, as well as with indirect herd protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
135
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(150 citation statements)
references
References 15 publications
13
135
0
2
Order By: Relevance
“…16 Rotavirus vaccination in countries with established vaccination programmes has consistently and significantly reduced the incidence of rotavirus gastroenteritis (RVGE) and associated hospitalizations, emergency department visits and outpatient/physician office visits in the United States (US), Europe and Australia. [17][18][19][20] Belgium introduced rotavirus vaccination in November 2006, with an uptake of 85% in the first year 21 and 89% in the second year. 22 This high vaccine uptake is maintained throughout subsequent years where parents are asked for a co-payment of the vaccine of 11.6€ per dose.…”
Section: Introductionmentioning
confidence: 99%
“…16 Rotavirus vaccination in countries with established vaccination programmes has consistently and significantly reduced the incidence of rotavirus gastroenteritis (RVGE) and associated hospitalizations, emergency department visits and outpatient/physician office visits in the United States (US), Europe and Australia. [17][18][19][20] Belgium introduced rotavirus vaccination in November 2006, with an uptake of 85% in the first year 21 and 89% in the second year. 22 This high vaccine uptake is maintained throughout subsequent years where parents are asked for a co-payment of the vaccine of 11.6€ per dose.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials and post-marketing studies demonstrated high efficacy (81%-100%) of both vaccines in preventing severe RVGE in infants in developed countries, 9,10 and significant reduction in RVGE disease burden in settings that introduced rotavirus immunization programs. [11][12][13][14] Though the World Health Organization recommends routine rotavirus vaccination for infants worldwide, rotavirus immunization has been introduced into childhood immunization programs in only a limited number of countries. [15][16][17] Among the barriers to universal rotavirus immunization is skepticism regarding the need and potential benefit of rotavirus immunization in reducing RVGE disease burden, vaccine safety concerns, and cost issues.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine effectiveness against gastroenteritis leading to hospitalization has been variable in NT; vaccine was estimated to be 77.7% effective during a 2007 G9P[8] outbreak ( 11 ) and 19% effective against a fully heterotypic G2P[4] strain in 2009 ( 12 ). Rotarix has been effective for decreasing rotavirus infection notification rates in Darwin, NT ( 10 ), and New South Wales ( 13 ). However, in 1 location in central NT, reported rotavirus infection rates have remained similar in the vaccine era to those in the prevaccine era ( 10 ), suggesting low vaccine uptake, low vaccine take, or waning immunity.…”
Section: Discussionmentioning
confidence: 99%